Pengaruh Penerapan GCG yang dinilai Menggunakan Corporate Governance Index, Kepemilikan Institusional, dan Kepemilikan Manajerial Terhadap Nilai Pasar Perusahaan - Galih R. Adinegara; Yudhi Herliansyah (Politeknik Ganesha Medan, 2023)
Intense business competition in the primary consumer goods sector in Indonesia has caused company management in this sector to always try to achieve efficiency and production so as to achieve maximum profit. However, to achieve this, companies sometimes issue operational policies that are contrary to applicable laws. Implementation of Good Corporate Governance (GCG) is urgently needed to avoid conflict of interest between company owners and management due to intense business competition in the sector. One tool to see the success of a company implementing GCG is the company's market value. This study uses a random effect model test to find out the relationship between GCG which is assessed using the corporate governance index (CGI), institutional ownership, and managerial ownership statistically influencing the market value of companies in the primary consumer goods sector listed on IDX from 2014 to 2019. Results of the study This shows that there is a negative relationship between the company's market value and the company's market value, while institutional and managerial ownership do not show significant results in statistical tests.